Household illness, poverty and physical and emotional child abuse victimisation: findings from South Africa’s first prospective cohort study - Meinck, F; Cluver, LD; Boyes, ME (Springer Science+Business Media, 2015)
Background Physical and emotional abuse of children is a large scale problem in South Africa, with severe negative outcomes for survivors. Although chronic household illness has shown to be a predictor for physical and emotional abuse, no research has thus far investigated the different pathways from household chronic illness to child abuse victimisation in South Africa.